2020
DOI: 10.1155/2020/2180708
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tyro3 IgG Associates with Disease Activity and Reduces Efferocytosis of Macrophages in New-Onset Systemic Lupus Erythematosus

Abstract: Background. Systemic lupus erythematosus (SLE) is a disease characterized by the production of a large number of autoantibodies. Defected phagocytosis of macrophage plays an important role in innate immunity in the pathogenesis of SLE. Tyro3 is a receptor responsible for the recognition of apoptotic cells during efferocytosis by macrophages. To investigate the role of Tyro3 receptor in macrophages’ efferocytosis of apoptotic cells in SLE, we aimed to reveal the clinical relevance and impact of Tyro3 autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…And Qin et al found that the plasma concentrations of sMer TK were elevated in primary Sjogren’s syndrome (pSS) patients and also associated with patient disease activity [ 18 ]. And autoantibody against Tyro3 TK was significantly increased in SLE patients compared to HCs and sTyro3 TK levels were also positively correlated with disease activity [ 19 ]. Research on pregnant women with positive antiphospholipid antibodies also suggested that the concentrations of sAxl TK were elevated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…And Qin et al found that the plasma concentrations of sMer TK were elevated in primary Sjogren’s syndrome (pSS) patients and also associated with patient disease activity [ 18 ]. And autoantibody against Tyro3 TK was significantly increased in SLE patients compared to HCs and sTyro3 TK levels were also positively correlated with disease activity [ 19 ]. Research on pregnant women with positive antiphospholipid antibodies also suggested that the concentrations of sAxl TK were elevated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…showed that anti-Tyro3 was associated with disease activity and the presence and impaired efferocytosis (65). We observe IgG (26%), IgM (2%) and IgA (11%) anti-SCARF1 antibodies in of SLE patients.…”
Section: Discussionmentioning
confidence: 55%
“…This may partially explain why mesenchymal stromal cell (MSC) injections reduce inflammation in mouse models of OA, as MSCs are cleared by synovial macrophages (42). Impaired efferocytosis is associated with worse disease activity in patients with systemic lupus erythematosus (43). In context with these and other studies, our findings suggest that synovial tissue macrophage dysfunction may be a key mechanism underlying the failure to resolve inflammation in knee OA.…”
Section: Discussionmentioning
confidence: 99%